Improving voltage stability in isolated renewable energy microgrids using virtual synchronous generators - Ahmad Supawi Osman; Aidil Azwin Zainul Abidin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
The integration of renewable energy systems (RES) and distributed generation (DG) into microgrids introduces significant challenges in maintaining voltage stability due to intermittent generation and reduced rotational inertia. This systematic review critically examines advanced control strategies aimed at enhancing voltage resilience in isolated RES-driven microgrids. Particular focus is placed on virtual synchronous generators (VSGs), which emulate electromechanical dynamics of synchronous machines via state-space modeling, and model predictive control (MPC), which enables real-time control optimization under multi-constraint scenarios. The review synthesizes literature on coupling–decoupling behavior, impedance sensitivity, and dynamic voltage response under varying load conditions. Additionally, it evaluates the role of hardware-in-the-loop (HIL) platforms and Runge-Kutta-based simulations in validating control models for real-time deployment. A structured framework is proposed, aligning VSG-based inertia emulation with predictive control to address voltage dips, oscillations, and transient instabilities. The findings highlight both theoretical gaps and implementation opportunities for achieving robust voltage stabilization in next-generation microgrids.